iScience 8 : student textbook - Aguilar, Delia R.; Del Rosario, Eileen L.; Pedernal, Jocelyn R.; Tadeja, Marissa E. (Cainta, Rizal : iBook Publishing, Inc., 2022)
This textbook entitled iScience 7: k to 12 curriculum series is published under iBook Publishing, Inc. It come in the series in kinder to grade 10 following the competencies of the k-12 program prescribed by the Department of Education. This book aims to provide the learners a repertoire of competencies important in knowledge -based society. The instructional activities aim to develop learner's critical problem solving and decision making ability, innovativeness and creativity, and effectiveness in communicating.
Includes bibliographical reference
English text
Keywords: study and learning